Analisis Hukum Terhadap Pembatalan Sertipikat Hak Atas Tanah Oleh Putusan Kepala Kantor Pertanahan Kota Medan No.80/Sk-12.71/VIII/2020 - Damanik, Diko Rolan; Limbong, Dayat; Ramadhan, M. Citra (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this paper is to analyze the law against the cancellation of land rights certificates (Case Study of Certificate Cancellation by the Decision of the Head of the Medan City Land Office No. 80/SK-12.71/VIII/2020 based on the Medan High Court Decision No. 366/PDT/2012/PT. MDN). In analyzing the problem formulation with normative juridical specifications, the approach is based on the statutory approach, the Synchronization approach, the library approach and the analytical approach. The sources of legal materials used are primary, secondary and tertiary sources of legal materials. The results and discussion found that the cause of the certificate of land rights being canceled by the authorized institution because it was declared an administrative law record or administrative record or invalid based on an error in its issuance in accordance with the provisions in Article 107 of the Regulation of the State Minister of Agrarian Affairs/Head of the National Land Agency (Permenag/KBPN). ) No. 9 of 1999 Jo. Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency no. 11 of 2016. Types of errors that result in administrative legal records as described in Article 107 of the Minister of Religion/KBPN No. 9 of 1999 are: a. procedural error, b. errors in the application of laws and regulations, c. subject error, d. object error, e. right type error, f. area calculation error, g. there is overlapping land rights, h. juridical data and physical data are incorrect or, i. other errors of an administrative law nature.